2017
DOI: 10.1097/mcg.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Provider, Patient, and Practice Factors Shape Hepatitis B Prevention and Management by Primary Care Providers

Abstract: Goals To evaluate provider knowledge, attitudes and barriers to HBV care and management practices across diverse primary care settings. Background Factors influencing adherence to recommended hepatitis B virus (HBV) screening and management guidelines are poorly defined. Methods Providers across various healthcare settings in San Francisco were surveyed. Multivariate analyses were used to identify factors associated with recommended HBV screening, vaccination, and disease monitoring. Results Of 277 (41.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 21 publications
(29 reference statements)
0
29
1
Order By: Relevance
“…Within our own health care system, a prior study found that 51% of patients with chronic hepatitis B had received HCC screening within the year . The rate of 20% without HCC screening in this HCV cohort, however, is higher than reported (10.2%) among patients with HBV …”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Within our own health care system, a prior study found that 51% of patients with chronic hepatitis B had received HCC screening within the year . The rate of 20% without HCC screening in this HCV cohort, however, is higher than reported (10.2%) among patients with HBV …”
Section: Discussioncontrasting
confidence: 50%
“…(21) The rate of 20% without HCC screening in this HCV cohort, however, is higher than reported (10.2%) among patients with HBV. (22) While we did not identify any particular factor that was significantly related to the lack of timely clinic visits or laboratory testing, the presence of cirrhosis was associated with receiving timely HCC screening among patients with advanced fibrosis. Further studies are needed to evaluate the role of other unmeasured patient and any provider factors contributing to the lack of optimal monitoring post-SVR in HCV.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The overall prevalence of HBsAg was 2.9% among refugees, representing an approximately 10 times higher burden of HBV infection than seen in the general U.S. population [3], confirming the need for early diagnosis and management of HBV infection among newly arriving refugees. Given the underdiagnosis of HBV infection by U.S. providers [22, 23], the refugee domestic health assessment is a key opportunity for early detection and prevention of HBV-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In real-life clinical practice, the diagnosis and treatment options of diseases are largely determined by the physicians; so, the level of primary physician's knowledge, training, and practice is closely related to the quality of medical services (6). Thus, this questionnaire-based survey was designed to assess the knowledge of junior doctors on the 2015 CHB guideline recommended by Chinese society of infectious diseases and Chinese society of hepatology, Chinese medical association.…”
Section: Objectivesmentioning
confidence: 99%